Association of betatrophin with metabolic characteristics in overweight/obese and lean women with PCOS. (4th March 2017) - Li, Linxia; Zhang, Feng; Cui, Jingjing; Shi, Yu; Xiang, Jiangdong; Wang, Xuejiao; Zhao, Naisi; Yan, Qingwu; Greenberg, Andrew S.; Peng, Yongde; Ding, Xiaoying
Abstract: As a new hormone, betatrophin has gained attention as a potential new target to combat insulin resistance (IR) and diabetes. Polycystic ovary syndrome (PCOS) is a common endocrine and metabolic disorder among women of the reproductive age with long term sequelae which include IR and metabolic syndrome. The aim of this study is to evaluate the circulating plasma betatrophin levels in overweight/obese or lean women with or without PCOS and also to elucidate possible correlations with anthropometric and metabolic parameters. Thirty-two patients with PCOS as well as fifty-three control subjects were enrolled after obtaining informed written consent. Clinical and biochemical parameters of all subjects were determined. Plasma adiponectin, GLP-1 and betatrophin levels were measured by ELISA. Plasma betatrophin levels were significantly increased in lean patients with PCOS compared with lean and obese controls. Moreover, in PCOS group, betatrophin levels were significantly negatively correlated with waist hip ratio (WHR), fasting insulin level (FINS) and HOMA-IR, whereas, significantly positively correlated with adiponectin level. Multiple regression analysis showed that HOMA-IR was an independent factor influencing serum betatrophin levels. Further follow-up studies are needed to highlight whether and how increased betatrophin secretion play an important role in IR and carbohydrates metabolism in patients with PCOS.